2007
DOI: 10.1002/adma.200701310
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Various Complex Patterned Structures From a Single Ellipsoidal Dot Prepattern by Capillary Force Lithography

Abstract: Parallel nanometer-scale patterning techniques such as edge lithography, [1] nanoimprint lithography (NIL), [2][3][4] soft lithography, [5,6] and combined lithography, referred to as capillary force lithography (CFL), [7][8][9][10][11] have recently attracted considerable attention because of high resolution and high reproducibility. These techniques replicate a pattern from a master mold prefabricated on a solid substrate by conformal contact without complicated equipment, leading to the fabrication of high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Techniques such as capillary force lithography (CFL) [63][64][65] exploit capillary forces to mold a polymer melt into the relief features of a patterned stamp. This procedure closely follows the earlier reported micromolding in capillaries (MIMIC) transfer process that exploits capillary wetting to fill a channel system with a liquid prepolymer that is subsequently cured (leaving a microstructured polymer feature on the substrate on removal of the mold).…”
Section: Methods Ii: Fabrication Of Masks With Discrete Features By Chmentioning
confidence: 99%
“…Techniques such as capillary force lithography (CFL) [63][64][65] exploit capillary forces to mold a polymer melt into the relief features of a patterned stamp. This procedure closely follows the earlier reported micromolding in capillaries (MIMIC) transfer process that exploits capillary wetting to fill a channel system with a liquid prepolymer that is subsequently cured (leaving a microstructured polymer feature on the substrate on removal of the mold).…”
Section: Methods Ii: Fabrication Of Masks With Discrete Features By Chmentioning
confidence: 99%
“…Capillary force, as one of the predominant forces at the nanometer size-scale, can be used not only to expedite micro-and nano-scale imprint lithography, but also to enable the formation of interesting and useful features on the lithographic products with details finer than those of the original molds [1][2][3][4][5][6][7][8]. These techniques take advantage of interfacial tension and wettability to control both the rate and the extent of the rising capillary and the resulting meniscus curvature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bruinink et al [3,4] have reported a technique of using the edge of a meniscus formed by capillary force lithography (CFL) as a mold of making second-generation stamps with increased resolution. Moreover, it has also been shown in CFL experiments that ring-like structures can be made taking advantage of the height variations of menisci formed in cylindrical capillaries [5,6]. However, it should be noted that only linear or ring-like structures have been reported to date; few experimental results have been reported with different cross-sectional geometries, even as simple as triangles or rectangles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 is a schematic representation of enhanced two-photon excited fluorescence (TPEF) DNA detection using large-area metal nanopatterns. To prepare a desired substrate, capillary force lithography (CFL) [22,23] was employed to fabricate metal nanopatterns with various feature sizes over a large, patterned area (2.7 mm  2.7 mm). We used the versatility of CFL to generate patterns of gold metal dots of diameter (D) 110 or 150 nm, with a period (S) of 250 nm.…”
mentioning
confidence: 99%
“…[11,15] It is noteworthy that the feature diameter of the gold dots can be further controlled by varying the reactive ion etching (RIE) time. [22] Various feature diameters (110-150 nm) of gold patterns can be prepared from a single dot (D ¼ 100 nm) pre-pattern by varying the RIE time from 10 to 20 s. The resulting gold patterns are defect-free over the entire area of 2.7 mm  2.7 mm, which is large enough to show a perfect, homogeneous spectral effect across the entire patterned substrate (see the Supporting Information, Figure S1). …”
mentioning
confidence: 99%